Analisis Usahatani Stroberi Di Strawberry Garden Tomohon - Tedang, Delvin; Loho, Agnes Estephina; Montolalu, Maya Hendrietta (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This research aims to evaluate the revenues and R/C Ratio of strawberry farming at Strawberry Garden Tomohon. The research was conducted over 3 months, from April to June 2024. The research method used is a survey with a case study approach. The data used in this research are primary data and secondary data. Primary data is data obtained from interviews with the owner of Strawberry Garden Tomohon including costs incurred for organic farming, production and prices of strawberry production facilities calculated for one year from April 2023 to March 2024, while secondary data is in the form of supporting data obtained from related agencies. The data analysis used is farming analysis. The results show that the total cost of strawberry farming at Strawberry Garden Tomohon for an area of 0.4 hectares total revenue was IDR 108,000,000 with total costs reaching IDR 81,789,486, resulting in total income of IDR 26,210,514 per year, with an R/C Ratio of 1.32.